2017
DOI: 10.1002/ehf2.12171
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic monitoring of cardiac status using heart sounds from an implanted cardiac device

Abstract: AimThe aim of this study was to evaluate the haemodynamic correlates of heart sound (HS) parameters such as third HS (S3), first HS (S1), and HS‐based systolic time intervals (HSTIs) from an implantable cardiac device.Methods and resultsTwo unique animal models (10 swine with myocardial ischaemia and 11 canines with pulmonary oedema) were used to evaluate haemodynamic correlates of S1, S3, and HSTIs, namely, HS‐based pre‐ejection period (HSPEP), HS‐based ejection time (HSET), and the ratio HSPEP/HSET during ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…Specifically, the third heart sound is detected in order to provide an objective measure of elevated filling pressure, while the first heart sound is taken as a surrogate for left ventricular contractility, as it has been shown to correlate with the maximum pressure derivative. 4 In agreement with previous studies, 5 we also observed higher values of respiratory rate at the time of HF events. Moreover, the continuous measurement of resting heart rate, in addition to its contribution to HeartLogic index calculation, allowed us to detect the recovery of fast atrioventricular conduction, therefore suggesting the need to implement new solutions in order to control the rate and ensure biventricular pacing delivery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Specifically, the third heart sound is detected in order to provide an objective measure of elevated filling pressure, while the first heart sound is taken as a surrogate for left ventricular contractility, as it has been shown to correlate with the maximum pressure derivative. 4 In agreement with previous studies, 5 we also observed higher values of respiratory rate at the time of HF events. Moreover, the continuous measurement of resting heart rate, in addition to its contribution to HeartLogic index calculation, allowed us to detect the recovery of fast atrioventricular conduction, therefore suggesting the need to implement new solutions in order to control the rate and ensure biventricular pacing delivery.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, the third heart sound is detected in order to provide an objective measure of elevated filling pressure, while the first heart sound is taken as a surrogate for left ventricular contractility, as it has been shown to correlate with the maximum pressure derivative 4. In agreement with previous studies,5 we also observed higher values of respiratory rate at the time of HF events.…”
Section: Discussionsupporting
confidence: 88%
“…The ability to measure S3 using sensors in implantable cardiac devices helps to overcome weaknesses by continuously monitoring S3 amplitudes, including both audible and subaudible components, and by providing objective quantification. An earlier canine study 6 demonstrated that devS3 is significantly correlated with changes in LAP and can detect elevated LAP with a specificity of 88%. This is consistent with a prior study 12 showing that phonocardiographic S3 amplitude is highly specific in detecting elevated left ventricular end-diastolic pressure in patients undergoing left-sided heart catheterization.…”
Section: Discussionmentioning
confidence: 98%
“…The device-measured heart sound (HS) signals have been shown to be feasible 5 and to be correlated with physiologic signals relevant to HF pathophysiology. 6 In an animal model, devS3 was significantly correlated with left atrial pressure (LAP) and was able to detect elevated LAP with high specificity. 6 However, it is unclear how well devS3 relates to traditional ausS3 and whether it is prognostic in ambulatory patients with HF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation